2005
DOI: 10.1097/01.olq.0000181148.80193.91
|View full text |Cite
|
Sign up to set email alerts
|

Control of Syphilis Outbreaks in Men Who Have Sex With Men: The Role of Screening in Nonmedical Settings

Abstract: These data suggest that even nontraditional, highly targeted screening programs conducted during outbreak situations do not detect many persons with syphilis, even though many of the screening venues were locations where men with syphilis met their sex partners. The low prevalence of infectious syphilis identified during these screening events suggests that the direct impact of these programs on decreasing syphilis transmission may be negligible. However, the secondary benefits, such as increasing awareness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 30 publications
1
19
0
1
Order By: Relevance
“…Lewis et al 29 described a number of sex venue–based screening events that identified 16 new syphilis diagnoses of all stages among 680 MSM (2.4%); the authors estimated that cost per new case identified ranged from $343 to $7451, although some programmatic costs may have been excluded. In a diverse geographic sample of MSM sex venue screenings, Ciesielski et al 25 screened more than 2500 MSM and identified a total of 34 new syphilis diagnoses (1.4%) and 29 early syphilis cases (1.2%). A large screening program in Georgia tested 8304 MSM from 2006 to 2010 and identified 332 early syphilis cases (4.0%) 39 ; all 332 were referred for syphilis partner services.…”
Section: Resultsmentioning
confidence: 99%
“…Lewis et al 29 described a number of sex venue–based screening events that identified 16 new syphilis diagnoses of all stages among 680 MSM (2.4%); the authors estimated that cost per new case identified ranged from $343 to $7451, although some programmatic costs may have been excluded. In a diverse geographic sample of MSM sex venue screenings, Ciesielski et al 25 screened more than 2500 MSM and identified a total of 34 new syphilis diagnoses (1.4%) and 29 early syphilis cases (1.2%). A large screening program in Georgia tested 8304 MSM from 2006 to 2010 and identified 332 early syphilis cases (4.0%) 39 ; all 332 were referred for syphilis partner services.…”
Section: Resultsmentioning
confidence: 99%
“…Community-based testing sites have attracted a subgroup of the population for testing that may have otherwise not tested in clinical settings in the USA and Brighton (UK) [83,84]. In Scotland (UK), providing results by telephone was shown to be cost effective and acceptable to men [85].…”
Section: Confirmed Diagnosismentioning
confidence: 97%
“…18 Ilustrativo de lo anterior es el informe reciente de que la prevalencia de nuevos casos de sífilis entre 14 143 homosexuales estudiados en Estados Unidos fue de 0.9%. 19 Por otra parte, la hipótesis del estudio se comprobó, toda vez que las prevalencias de sífilis registradas en publicaciones previas para diversos grupos de la población mexicana, como sexoservidoras, mujeres asistentes de servicios ginecológicos, embarazadas, parejas de individuos seropositivos al VIH y hombres que tienen sexo con hombres, [6][7][8][9][10][11][20][21][22] hacían esperar que un estudio de base poblacional reflejara la real magnitud de la infección. También ha resultado interesante la posibilidad de precisar las seroprevalencias de anticuerpos antitreponémicos en función de su distribución geográfica en el país; con ello fue factible reconocer en principio que la región sur es la más importante para poner en práctica medidas de control y prevención de la sífilis de una manera ponderada.…”
Section: Discussionunclassified